PPAR-γ activation promotes xenogenic bioroot regeneration by attenuating the xenograft induced-oxidative stress - Tingting Lan; Fei Bi; Yuchan Xu; Xiaoli Yin; Jie Chen; Xue Han; Weihua Guo (Nature Publishing Group, 2023)
Abstract Xenogenic organ transplantation has been considered the most promising strategy in providing possible substitutes with the physiological function of the failing organs as well as solving the problem of insufficient donor sources. However, the xenograft, suffered from immune rejection and ischemia-reperfusion injury (IRI), causes massive reactive oxygen species (ROS) expression and the subsequent cell apoptosis, leading to the xenograft failure. Our previous study found a positive role of PPAR-γ in anti-inflammation through its immunomodulation effects, which inspires us to apply PPAR-γ agonist rosiglitazone (RSG) to address survival issue of xenograft with the potential to eliminate the excessive ROS. In this study, xenogenic bioroot was constructed by wrapping the dental follicle cells (DFC) with porcine extracellular matrix (pECM). The hydrogen peroxide (H2O2)-induced DFC was pretreated with RSG to observe its protection on the damaged biological function. Immunoflourescence staining and transmission electron microscope were used to detect the intracellular ROS level. SD rat orthotopic transplantation model and superoxide dismutase 1 (SOD1) knockout mice subcutaneous transplantation model were applied to explore the regenerative outcome of the xenograft. It showed that RSG pretreatment significantly reduced the adverse effects of H2O2 on DFC with decreased intracellular ROS expression and alleviated mitochondrial damage. In vivo results confirmed RSG administration substantially enhanced the host's antioxidant capacity with reduced osteoclasts formation and increased periodontal ligament-like tissue regeneration efficiency, maximumly maintaining the xenograft function. We considered that RSG preconditioning could preserve the biological properties of the transplanted stem cells under oxidative stress (OS) microenvironment and promote organ regeneration by attenuating the inflammatory reaction and OS injury.